192 'Immune-brain': a case series of cognitive dysfunction/decline in cancer patients on immunotherapy. (9th November 2020) - Gillett, Sarah; Jordan-Bruno, Ximena; Rehman, Hibba; Thomas, Alissa; Gillett, Sarah
Abstract : Background: Immunotherapy agents are now the standard of care for many types of malignancies and use of checkpoint inhibitor immunotherapy (IO) is widespread across oncology. Cognitive dysfunction/decline (CD) is a well-known side effect of conventional chemotherapy (i.e. 'chemo-brain'), but the neuro-cognitive impact of checkpoint inhibitor immunotherapy (IO) is not well described, despite the known potential for inflammatory neurotoxicities and encephalitis. Though high grade neurologic events are reported in <1% of patients receiving IO, less severe or possibly transient neurocognitive effects that do not lead to formal neuropsychological evaluation are probably under-reported. Combination of IO with other anti-cancer modalities like cytotoxic chemotherapy and radiation could theoretically compound neurotoxicity through neuroinflammation. Methods: From January 2015-Decmber 2018 at University of Vermont Medical Center, we retrospectively identified cancer patients who received at least one infusion of IO and had a concurrent diagnosis of CD on the problem list, medical history, or billing codes. We used the search terms: cognitive impairment, mild cognitive impairment, neurodegenerative cognitive impairment, memory change/memory deficit/memory difficulty/memory impairment, altered mental status, or encephalopathy to define cognitive impairment. We manually reviewed the charts of all patients meeting this criteria and excluded patients with an alternative diagnosis that was causal for CD (stroke, sepsis, seizure, brain tumor). Results: We identified 55 patients and excluded 16 for CD before IO started, 23 with toxic/metabolic causes (including stroke, sepsis, medications, seizures), 4 for primary central nervous system malignancy, and 6 for CD related to new or worsening brain metastases. Six had CD possibly related to IO (table 1). Most had also received chemotherapy either concurrently or prior to starting IO, but two patients had only ever received IO cancer therapy. Four of the six had documented MMSE or neuropsychological testing. On careful chart review, no alternative diagnosis was identified as clearly causal for the change in cognition. Conclusions: Patients receiving IO cancer therapy do report CD, which has not been broadly described. Though our data is corollary, it opens the question as to whether prospective pre- and post-treatment cognitive monitoring may identify more patients with neurocognitive symptoms related to immunotherapy. Future research is needed to report incidence of potential IO-related CD and to develop preventative or therapeutic strategies.